ECO-SPORT TOURISM IN GUNUNG GEDE PANGRANGO NATIONAL PARK - Tengku, Habib Arrasyid; Sunarminto, Tutut; Kosmaryandi, Nandi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Eco-sport tourism is an integrated activity between ecotourism and sports. The human need for travel to refresh the soul and mind is as important as the need to nourish the physical condition through sports activities. The research aims to analyze the potential and demand for eco-sport tourism. The research was conducted in March-July 2022 at TNGGP, West Java Province. The results showed the availability of tourism resources in TNGGP including waterfalls, campsites, lakes or ponds, natural phenomena, suspension bridges, bird watching trails and conservation education centers. Tourism resources in TNGGP have the potential to be used for eco-sport tourism activities as objects and places of activity. The assessment of active sport tourism by managers is dominated by the knowledge part with a score of 6.79, while sport event tourism with a score of 6.71, and nostalgia for sport tourism 6.58. Key words: Ecotourism, Sports Ecotourism, Conservation Areas